Электротехника, радиотехника ва электроника фанини ўқитишда амалий машғулотларнинг такомиллашти- рилган мазмуни (SCIENCE and SOCIETY, 2018)
The article contains recommendations to use new teaching methods in increasing the quality of teaching in higher education. The main purpose of these recommendations is using of information technologies for the development of skills and habits in teaching.